Analisis Word of Mounth dan Truth terhadap Minat Haji Khusus (Studi di Dewangga Lil Hajj Wal Umrah Surakarta) - Nury Salma; Ade Yuliar (UIN Raden Mas Said Surakarta, 2020)
This study aims to analyze the effect of word of mouth and trust towards the interest of pilgrims to register exclusive Hajj in Dewangga Lil Hajj Wal Umrah Surakarta. The dependent variable in this study is the interest of pilgrims registering exclusive hajj. Meanwhile, the independent variables are word of mouth and service trust. The population in this study included all pilgrims who have registered a special Hajj package. The sample was selected using the accidental sampling method and obtained 30 respondents. This study was a quantitative study using multiple linear regressions as an analysis technique. The results show that word of mouth has no significant effect on the interest of pilgrims registering exclusive hajj. Furthermore, the truthÂ has a significant effect on the readability of pilgrims registering exclusive hajj.